CIVISTI – A forward-looking method based on citizens’ visions - Sotoudeh, Mahshid; Gudowsky, Niklas (Uniwersytet im. A. Mickiewicza w Poznaniu Wydział Nauk Społecznych, Instytut Filozofii UAM, 2016)
In this paper, we present the forward-looking CIVISTI method with strong participatory elements for inter- and transdisciplinary futures research based on citizens’ visions. This multi- perspective demand side approach, has been developed and implemented since 2008 in different projects at EU, national and local level for knowledge-based policy advice mainly focussed on program development. Applying CIVISTI (Citizens Visions on Science Technology and Innovation) provides desirable futures that incorporate people’s hopes and fears and provides insights to societal challenges and values. It furthermore combines this knowledge with experts’ and stakeholders’ recommendations for implementation.
Keywords: forward-looking; sustainable development; participation; citizen visions; inter- and trans-disciplinary knowledge generation